2021
DOI: 10.1021/acs.cgd.1c00504
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Droplet Consumption in Vapor–Liquid–Solid III–V Nanowire Growth

Abstract: We study experimentally and theoretically the consumption of the apical gallium droplet that mediates the self-catalyzed vapor-liquid-solid growth of GaP nanowires. Consumption is achieved after growth by providing only phosphorous and its progress is monitored ex situ in nanowire arrays fabricated by molecular beam epitaxy. We develop detailed calculations of the process, taking into account four channels of liquid gallium consumption. These include the formation of GaP using phosphorous delivered to the drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
(115 reference statements)
0
12
0
2
Order By: Relevance
“…Control of such structures at the ML level is actually necessary for promising applications. [44][45][46] Note that if group V sidewall diffusion contributed to droplet refill, [35] this would only require stems longer than the corresponding diffusion length, in addition to constant NW and droplet radii. [36,47] We showed that the reason for this quasideterministic growth regime is the compensation between the propagation time and preceding waiting time, expected to occur when there is never enough group V atoms in the catalyst particle to produce a full ML at nucleation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Control of such structures at the ML level is actually necessary for promising applications. [44][45][46] Note that if group V sidewall diffusion contributed to droplet refill, [35] this would only require stems longer than the corresponding diffusion length, in addition to constant NW and droplet radii. [36,47] We showed that the reason for this quasideterministic growth regime is the compensation between the propagation time and preceding waiting time, expected to occur when there is never enough group V atoms in the catalyst particle to produce a full ML at nucleation.…”
Section: Discussionmentioning
confidence: 99%
“…At given temperature T, the state of the binary liquid is set by the atomic concentration x of As. The numbers of Ga and As atoms removed from the liquid to form any amount of the solid NW are equal, and we consider constant and equal rates of refilling of the droplet for Ga and As (by the direct and re-emitted beams [10,[33][34][35] and by surface diffusion, [36] which might even operate for group V species [35] ). We assume constant NW radius and droplet contact angle.…”
Section: Modelmentioning
confidence: 99%
“…The predeposition time, i.e. the time during which Ga flux is on, as well as the substrate temperature, 24 determine the droplet volume. This step is crucial as the volume of the droplet is one of the determining parameters for the contact angle, defined as β , discussed later in this section.…”
Section: Electron-beam Lithographymentioning
confidence: 99%
“…Ясно, однако, что диффузионная длина адатомов группы V на поверхности не может быть нулевой (в противном случае эти адатомы вообще не могли бы десорбироваться в составе димеров As 2 , P 2 или N 2 ). Недавно в работе [17] была рассмотрена диффузия адатомов P по боковой поверхности ННК GaP на расстояния до 400 nm. Вполне возможно также, что радиальный рост ННК [8,11,13,14] вне зависимости от типа катализатора или его отсутствия может контролироваться потоком элемента группы V. Целью настоящей работы является построение простой модели для скорости роста слоев III−V за счет поверхностной диффузии обоих элементов, а также установление условий, при которых рост действительно контролируется диффузией адатомов группы III.…”
unclassified